Designing new ferrite/manganite nanocomposites. Issue 4 (24th December 2015) - Muscas, G.; Anil Kumar, P.; Barucca, G.; Concas, G.; Varvaro, G.; Mathieu, R.; Peddis, D.
Abstract : Two nanocomposites of La0.67 Ca0.33 MnO3 and CoFe2 O4 oxides have been prepared by mechanical mixing (left) and a core/shell-like (right) approach, producing specific magnetic and magnetoresistive behaviors. Abstract : Two kinds of nanocomposites of transition metal oxides were synthesized and investigated. Each nanocomposite comprises nanoparticles of La0.67 Ca0.33 MnO3 and CoFe2 O4 in similar volume fractions, however arranged with different morphologies. The temperature-dependent magnetic and electrical properties of the two systems are found to greatly differ, suggesting different degrees of interaction and coupling of their constituents. This is confirmed by magnetic field-dependent experiments, which reveal contrasted magnetization reversal and magnetoresistance in the systems. We discuss this morphology–physical property relationship, and the possibility to further tune the magnetism and magneto-transport in such nanocomposites.